2019
DOI: 10.1093/jxb/erz136
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-dependent regulation of sweet pepper fruit ripening

Abstract: Ripening is a complex physiological process that involves changes in reactive nitrogen and oxygen species that govern the shelf-life and quality of fruits. Nitric oxide (NO)-dependent changes in the sweet pepper fruit transcriptome were determined by treating fruits at the initial breaking point stage with NO gas. Fruits were also harvested at the immature (green) and ripe (red) stages. Fruit ripening in the absence of NO resulted in changes in the abundance of 8805 transcripts whose function could be identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 109 publications
(116 reference statements)
3
109
0
Order By: Relevance
“…This is corroborated by the increase in protein nitration (Chaki et al ), S ‐nitrosation (Rodríguez‐Ruiz et al ) and lipid peroxidation observed in sweet pepper fruit (Chu‐Puga et al ). Furthermore, it has been shown that the exogenous NO gas application on sweet pepper fruit has an anti‐maturation effect because it reduced the content of oxidative stress marker such as lipid peroxidation whereas antioxidant systems increased including ascorbate and glutathione content as well as the ascorbate peroxidase activity (Rodríguez‐Ruiz et al , González‐Gordo et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is corroborated by the increase in protein nitration (Chaki et al ), S ‐nitrosation (Rodríguez‐Ruiz et al ) and lipid peroxidation observed in sweet pepper fruit (Chu‐Puga et al ). Furthermore, it has been shown that the exogenous NO gas application on sweet pepper fruit has an anti‐maturation effect because it reduced the content of oxidative stress marker such as lipid peroxidation whereas antioxidant systems increased including ascorbate and glutathione content as well as the ascorbate peroxidase activity (Rodríguez‐Ruiz et al , González‐Gordo et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, NADPH oxidase (Rboh) activity involved in superoxide generation increased 5.3‐fold, which closely correlates with an increase in lipid peroxidation, a marker of oxidative stress associated with fruit ripening (Chu‐Puga et al ). On the other hand, proline (Pro) content, whose biosynthesis from glutamate by the Δ 1 ‐pyrroline 5‐carboxylate synthase (P5CS) enzyme specifically requires NADPH, has also been reported to increase during ripening (Signorelli and Monza , González‐Gordo et al ). It is important to note that the increase in Pro is related to the mechanisms of response to different plant stresses usually associated with oxidative stress conditions such as salinity (Bouthour et al 2015), drought (Signorelli et al ) or arsenic (Rodríguez‐Ruiz et al ), although Pro is not a direct scavenger of ROS (Signorelli et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Both types of Trx regulate chloroplast redox homeostasis and interact with Prxs to establish a redox signal cascade and to modulate thiol groups [36]. A Trx combined with nitroreductase (NTR)at the C terminus is called NTRC, which, when involved in redox regulation, appears to affect starch and chlorophyll biosynthesis [41]. 1 O 2 scavenging chiefly occurs through reactions with biomolecules such as tocopherols [42], carotenoids [43], and membrane lipids [44].…”
Section: Enzymatic and Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…As outlined above, ROS and NO play a crucial role in signaling mechanisms, which modulate plant growth and development, transpiration, hormonal regulation, germination, stomatal gaseous exchange, flowering, fruit ripening, defense responses, and programmed cell death (PCD) [41].…”
Section: Ros and No Intermediates In Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation